Mono- or di-substituted imidazole derivatives for inhibition of acetylcholine and butyrylcholine esterases - Kuzu, Burak; Tan, Meltem; Taslimi, Parham; Gülçin, İlhami; Taşpınar, Mehmet; Menges, Nurettin; Taslimi, Parham (Bioorganic Chemistry, 2019)
Mono- or di-substituted imidazole derivatives were synthesized using a one-pot, two-step strategy. All imidazole derivatives were tested for AChE and BChE inhibition and showed nanomolar activity similar to that of the test compound donepezil and higher than that of tacrine. Structure activity relationship studies, docking studies to on X-ray crystal structure of AChE with PDB code 1B41, and adsorption, distribution, metabolism, and excretion (ADME) predictions were performed. The synthesized core skeleton was bound to important regions of the active site of AChE such as the peripheral anionic site (PAS), oxyanion hole (OH), and anionic subsite (AS). Selectivity of the reported test compounds was calculated and enzyme kinetic studies revealed that they behave as competitive inhibitors, while two of the test compounds showed noncompetitive inhibitory behavior. ADME predictions revealed that the synthesized molecules might pass through the blood brain barrier and intestinal epithelial barrier and circulate freely in the blood stream without binding to human serum albumin. While the toxicity of one compound on the WS1 (skin fibroblast) cell line was 1790?µM, its toxicity on the SH-SY5Y (neuroblastoma) cell line was 950?µM.
Keywords: SAR; Docking; Alzheimer’s disease; Water solubility; ADME; Enzyme kinetic study